2014
DOI: 10.2174/1389450115666140714121514
|View full text |Cite
|
Sign up to set email alerts
|

New Use for Old Drugs? Prospective Targets of Chloroquines in Cancer Therapy

Abstract: During the last decade research is gradually repositioning the antimalarial drug chloroquine, and certain related quinoline derivatives, as anticancer agents. Chloroquine and hydroxychloroquine, in particular, have relatively well-characterized toxicity profiles due to several decades of use for treatment of malaria. Previously published review articles provide an excellent overview of the diversity of chloroquine effects on cancer cells, both in the cell culture as well as on human tumors grafted into mice; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 0 publications
2
46
0
1
Order By: Relevance
“…Defects in autophagy are associated with susceptibility to metabolic stress, genomic damage and tumorigenesis, indicating a role of autophagy in tumor suppression [37]. On the other hand, autophagy can promote the growth of established tumors [38] making autophagy process a double-edged sword [39,40]. Our results support the hypothesis that titanocenes may cause ER stress followed by autophagy induction.…”
Section: Discussionsupporting
confidence: 81%
“…Defects in autophagy are associated with susceptibility to metabolic stress, genomic damage and tumorigenesis, indicating a role of autophagy in tumor suppression [37]. On the other hand, autophagy can promote the growth of established tumors [38] making autophagy process a double-edged sword [39,40]. Our results support the hypothesis that titanocenes may cause ER stress followed by autophagy induction.…”
Section: Discussionsupporting
confidence: 81%
“…Conceivably, due to the intense replication of this parasite during acute infection, it could be strongly affected by DNA damage or free radicals. Indeed, reports in the literature have indicated that anti-cancer drugs that affect cellular proliferation can be used as anti-microbial agents because both cell types share common behaviors concerning their high proliferative capabilities [27][28][29]. Indeed, a recent work evidenced the antileishmanial actions of other two isobenzofuranone derivatives and indicated that these actions were due to the induction of reactive oxygen species (ROS)-mediated apoptosis-like cell death and the inhibition of topoisomerases [30].…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of the proteasome [8], or epigenetic reprogramming via a deacetylase inhibitor [144], may lead to activation of homeostatic responses and NF-κB, and rescue a malignant cell from antineoplastic treatments. One such example is the induction of lysosome activity after inhibition of the proteasome: this is not only a trigger for lysosome-dependent degradation of IκB, but it can also result in rescue of the cancer cell through autophagy, which enables it to survive by recycling many of its contents [145]. It is therefore important to target therapeutic intervention to the drug-induced metabolic pathway that rescues the malignant cell.…”
Section: Homeostatic Challenges: Impact On Nf-κb Activity In Solidmentioning
confidence: 99%